Possessão e exorcismo: os múltiplos aspectos de um fenômeno - Paiva, Luiz Henrique Rodrigues (2015)
This work aims to present the phenomenon of possession and exorcism in the Judeo-Christian tradition throughout history; starting from the Jewish antiquity to the present day. Demonic possession, as well as the practice of exorcism, are studied themes from antiquity to the present day. It is intended to provide a summary, in historiographical key, these phenomena of Religious Realm, and a critical analysis supported in studies by scholars like Karl Kertelge, Antonio Lazarini Neto, José Irenaeus Rabuske and Luigi Schiavo and historians as Jaccques Le Goff and Jean Delumeau . For this to be done, the work was divided into three chapters: the first, we analyze the question of the historical overview of the phenomenon; in the second, portray the developments in the phenomenon suffered by the beliefs of the medieval and modern world, culminating in the theological analysis of the possession and exorcism phenomenon in the last chapter.